PENJATIDIRIAN MASYARAKAT MELALUI PENDIDIKAN KARAKTER BANGSA DAN PEMERINTAH NEGARA MARITIM - Susdarwono, Endro Tri; Anis, Aswhar (Badan Perencanaan Pembangunan Penelitian dan Pengembangan Daerah Kabupaten Cilacap, 2024)
This research aims to provide a description of community identity through national character education and maritime government. This identity can be seen from the understanding regarding the character of the nation and the government of maritime countries that is developing in society. The approach used in the research is a combination research using a concurrent triangulation design. The research locus is in Cilacap Regency, Kebumen Regency, Pemalang Regency, and Tegal City. The data collection technique uses a questionnaire with random sampling type, while the data analysis technique uses hypothesis testing, the independence testing method, the Kruskall-Wallis method, and the Wilcoxon stratified level method. This research concludes that people's understanding of the character of the nation and the character of the government of maritime countries is influenced by the level of education. However, there are differences in this understanding for people living in rural, urban and coastal areas. For coastal communities themselves, there is no difference in understanding between people living on the north coast and those on the south coast.